The relationship between consumer, clinician, and organizational characteristics and use of evidence-based and non-evidence-based therapy strategies in a public mental health system. (December 2017) - Beidas, Rinad; Skriner, Laura; Adams, Danielle; Wolk, Courtney Benjamin; Stewart, Rebecca E.; Becker-Haimes, Emily; Williams, Nathaniel; Maddox, Brenna; Rubin, Ronnie; Weaver, Shawna; Evans, Arthur; Mandell, David; et al.
Abstract: We investigated the relationship between consumer, clinician, and organizational factors and clinician use of therapy strategies within a system-wide effort to increase the use of cognitive-behavioral therapy. Data from 247 clinicians in 28 child-serving organizations were collected. Clinicians participating in evidence-based practice training initiatives were more likely to report using cognitive-behavioral therapy when they endorsed more clinical experience, being salaried clinicians, and more openness to evidence-based practice. Clinicians participating in evidence-based practice initiatives were more likely to use psychodynamic techniques when they had older clients, less knowledge about evidence-based practice, more divergent attitudes toward EBP, higher financial strain, and worked in larger organizations. In clinicians not participating in evidence-based training initiatives; depersonalization was associated with higher use of cognitive-behavioral; whereas clinicians with less knowledge of evidence-based practices were more likely to use psychodynamic techniques. This study suggests that clinician characteristics are important when implementing evidence-based practices; and that consumer, clinician, and organizational characteristics are important when de-implementing non evidence-based practices. This work posits potential characteristics at multiple levels to target with implementation and deimplementation strategies. Highlights: The City of Philadelphia is implementing cognitive-behavioral therapy (CBT). We investigate the contribution of contextual factors on therapist use of CBT. Clinician and organizational factors predicted use of CBT. Targets for future strategies to improve the implementation of CBT are suggested.